2019
DOI: 10.7717/peerj.7029
|View full text |Cite
|
Sign up to set email alerts
|

Water regime and osmotic adjustment under warming conditions on wheat in the Yaqui Valley, Mexico

Abstract: An experiment was carried out to evaluate the effect of increased temperature on roots and leaf water and osmotic potential, osmotic adjustment (OA) and transpiration on Triticum durum L. (CIRNO C2008 variety) during growth (seedling growth), tillering and heading phenophases. Wheat was sown under field conditions at the Experimental Technology Transfer Center (CETT-910), as a representative wheat crop area from the Yaqui Valley, Sonora México. Thermal radiators were placed at 1.20 m from the crop canopy. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Osmotic water potential significantly decreased in D-09013, Bhakhar-2011, and BRC-390, which meant that these genotypes could have better adaptability while under combined stress, it decreased in all. The previous finding revealed that in plants, under abiotic stresses (heat and drought), a decrease in osmotic potential was observed by accumulating, osmotically active, low molecular weight compounds (osmolytes) such as glycine betaine (GB), proline, and reduced glutathione (RG) in chickpea tolerant genotypes (Argentel-Martínez et al, 2019 ; Makonya, 2020 ). The pressure exerted against the plant cell wall by protoplast is termed as turgor potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osmotic water potential significantly decreased in D-09013, Bhakhar-2011, and BRC-390, which meant that these genotypes could have better adaptability while under combined stress, it decreased in all. The previous finding revealed that in plants, under abiotic stresses (heat and drought), a decrease in osmotic potential was observed by accumulating, osmotically active, low molecular weight compounds (osmolytes) such as glycine betaine (GB), proline, and reduced glutathione (RG) in chickpea tolerant genotypes (Argentel-Martínez et al, 2019 ; Makonya, 2020 ). The pressure exerted against the plant cell wall by protoplast is termed as turgor potential.…”
Section: Discussionmentioning
confidence: 99%
“…Genotypic performance (how it differs from average genotype) can be estimated by the distance of genotype from the origin of the biplot, distant genotypes could have maximum values for one or more traits. Pearson correlation between traits were indicated by cosine angle between two traits, i.e., no correlation = angle of 90 • : positive correlation =<90 • : negative correlation =>90 • (Argentel- Martínez et al, 2019). Under irrigation treatment genotypes, D-09013 was a distant genotype and positive correlation was observed among POD, yield, RWC, TOS, APX, TSP, and TPC.…”
Section: Principal Component Biplot Analysismentioning
confidence: 99%
“…Therefore, differences in mineral nutrient contents were probably more related to a still unknown heat-induced adaptation mechanism (and/or to the effect caused by the interaction between nutrients) than to a direct effect caused by nutrient dilution. The effect of heat stress on cellular osmotic adjustments due to the increased transpiration rates when elevated temperatures occur should also not be discounted; this could result in increments in the mineral and protein content [ 59 , 60 ]. Interestingly, the mineral composition of quinoa straw was richer from a nutritional perspective compared with the mineral composition of cereal straws commonly used for animal feed [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, many genes were identified to be involved in the metabolism of these osmolytes. Osmotically active solutes (osmolytes) are induced for the maintenance of cellular functions through biosynthesis of different substances as well as enzyme activity and proteins 86 . In the current study, proline, trehalose, and glycine betaine were found to have a relation in combating drought stress.…”
Section: Discussionmentioning
confidence: 99%